Auditor Business, Audit Committee, Report Quality: Intervening Effect of Audit Delay - Tanujaya, Kennardi; Evelyn, Vinvin; Ivone, I (Universitas Pendidikan Indonesia, 2024)
This research analyzes the effect of auditor busyness and audit committee characteristics on financial reporting quality, with audit delay as a mediating variable. This research is quantitative and uses panel regression data as an analysis method. Listed cyclical goods companies in the Indonesia Stock Exchange are used as the sample data, ranging from 2018-2022, with 375 samples. The results from this research show no significant influence between auditor busyness and the characteristics of the audit committee on the financial reporting quality, with audit delay as a mediating variable. However, audit committee size and meetings show a significant positive influence on audit delays. Meanwhile, a significant positive impact was also found between audit delay and the quality of financial reports. The outcomes of this research are expected to benefit companies and investors in understanding some factors that cause audit delays. It is also expected to give investors a better understanding of where audit delay indicates doubts about the quality of financial reports. Research about auditor busyness is scarce, especially in Indonesia, and this study is the first in Indonesia to examine the factors that affect financial reporting quality, with audit delay as an intervening variable due to the importance of financial reporting quality as it is used for decision-making.